2020
DOI: 10.3390/jcm9020300
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Landscape of Nonobstructive Azoospermia and New Perspectives for the Clinic

Abstract: Nonobstructive azoospermia (NOA) represents the most severe expression of male infertility, involving around 1% of the male population and 10% of infertile men. This condition is characterised by the inability of the testis to produce sperm cells, and it is considered to have an important genetic component. During the last two decades, different genetic anomalies, including microdeletions of the Y chromosome, karyotype defects, and missense mutations in genes involved in the reproductive function, have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 222 publications
0
54
0
Order By: Relevance
“…We previously demonstrated that Cracd mRNA is expressed in adult mouse testis within the germ cells [ 8 ]. To further define the transcriptional temporal profile and uncover when and where within mouse spermatogenesis Cracd mRNA is initially expressed, we used in situ hybridization to map Cracd in staged postnatal, juvenile (P5-4 weeks), and adult (4-month-old) C57BL/6J mice [ 1 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that Cracd mRNA is expressed in adult mouse testis within the germ cells [ 8 ]. To further define the transcriptional temporal profile and uncover when and where within mouse spermatogenesis Cracd mRNA is initially expressed, we used in situ hybridization to map Cracd in staged postnatal, juvenile (P5-4 weeks), and adult (4-month-old) C57BL/6J mice [ 1 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Azoospermia, a condition in which there are no spermatozoa in the ejaculate, occurs in approximately 1% of all men and ranges between 10% and 15% among infertile men [ 7 ]. Moreover, azoospermia may occur because of an obstruction in the reproductive tract (called obstructive azoospermia) or the more prevalent condition of inadequate spermatozoa nor late-stage spermatids production (called non-obstructive azoospermia) which results in male infertility [ 8 ]. Given that non-obstructive azoospermia is most likely related to a failure in the spermatogenic process, we need to focus on identifying and further understanding the genes involved in testicular spermatogenesis and aberrant signaling pathways that cause male infertility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatogenesis is a polygenic and multistep process that involves a variety of regulatory molecules (Wang et al., 2018; Yuan et al., 2019). NOA represents the most severe male infertility condition, and various genetic anomalies have been reported to be involved in the progression of disease (Cervan‐Martin et al., 2020; Vogt et al., 2019). With a complex genetic background, the pathogenesis of INOA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Azoospermia can be divided into two main categories: mechanical obstruction of vas deferens (obstructive azoospermia, OA) and primary spermatogenic failure (nonobstructive azoospermia, NOA). Approximately 60% of azoospermia patients are diagnosed with NOA (Cissen et al., 2016) and the common causes are primary testicular factors, including genetic mutations, karyotype aberrations, Y chromosome microdeletions, hypergonadotropic hypogonadism and varicocele (Cervan‐Martin, Castilla, Palomino‐Morales, & Carmona, 2020; Yatsenko et al., 2015). However, only about 25% of the NOA cases can be attributed to the above reasons, and the aetiology of the remaining patients is still unclear and in those patients, it is defined as idiopathic nonobstructive azoospermia (INOA; Alfano et al., 2019; Cissen et al., 2016).…”
Section: Introductionmentioning
confidence: 99%